2015
DOI: 10.5194/bg-12-1415-2015
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ra isotopes to deduce rapid transfer of sediment-derived inputs off Kerguelen

Abstract: Abstract. The Southern Ocean is known to be the largest high-nutrient, low-chlorophyll (HNLC) region of the global ocean due to iron limitation. However, a large phytoplankton bloom develops annually downstream of the Kerguelen Islands, a bloom which is sustained partly by iron released from the sediments deposited onto the shelves. In the framework of the KEOPS-2 project, we used radium isotopes ( 224 Ra, T 1/2 = 3.66 d; 223 Ra, T 1/2 = 11.4 d; 228 Ra, T 1/2 = 5.75 yr) to provide information on the origin of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 47 publications
(69 reference statements)
2
21
0
Order By: Relevance
“…Moreover, Bowie et al (2014) showed that atmospheric inputs were of the order of 50 nmol m −2 d −1 , which is insignificant compared to the lateral supply of dFe in the same area (180-2400 nmol m −2 d −1 ). Significant 224 Ra and 223 Ra activities were detected in offshore waters south of the PF (Sanial et al, 2015). These observations clearly indicated that dissolved sediment-derived inputs of Ra can be rapidly transferred towards offshore waters.…”
Section: Recirculation Area (Cluster 3)mentioning
confidence: 74%
“…Moreover, Bowie et al (2014) showed that atmospheric inputs were of the order of 50 nmol m −2 d −1 , which is insignificant compared to the lateral supply of dFe in the same area (180-2400 nmol m −2 d −1 ). Significant 224 Ra and 223 Ra activities were detected in offshore waters south of the PF (Sanial et al, 2015). These observations clearly indicated that dissolved sediment-derived inputs of Ra can be rapidly transferred towards offshore waters.…”
Section: Recirculation Area (Cluster 3)mentioning
confidence: 74%
“…By this process, subsurface water is becoming enriched in iron, which subsequently can be efficiently supplied to the mixed layer via vertical mixing Park et al, 2008). At the polar front, iron fertilization results from the previously described enrichment over the plateau and the spreading of this enrichment eastward through the additional interaction between the polar front jet and local bathymetry (Mongin et al, 2008;Sanial et al, 2015). This mode of supply can be compared with the polar-front-associated bloom in the Atlantic sector, where iron is supplied by lateral advection from the Patagonian shelves and islands in the Scotia Ridge area (de Baar et al, 1995;Löscher et al, 1997) or by direct lithogenic aerosol deposition (Quéguiner et al, 1997).…”
Section: High Primary Production In Naturally Iron-fertilized Bloomsmentioning
confidence: 97%
“…In order to estimate iron delivery due to horizontal stirring, we use an advection scheme based on altimetry, extending to the Southern Ocean a Lagrangian model used for predicting the development of the Kerguelen phytoplanktonic plume . The model has been extensively calibrated and validated in the Crozet and Kerguelen regions by integrating satellite data (altimetry and ocean color), lithogenic isotopes, iron measurements, and drifters Sanial et al, 2014Sanial et al, , 2015. model seeds each open ocean location with a particle and finds the particle's most recent contact with a shallow bathymetry by a back trajectory issued from altimetry data.…”
Section: Lagrangian Modeling Of Horizontal Iron Fluxesmentioning
confidence: 99%